Development of Tourism in Hill Area of Uttar Pradesh - Planning Commission (Planning Commission, 1973)
The problem of accelerating the development of hill areas of Uttar Pradesh has been a matter of concern for the State Government as well as the Government of India, It has, in this connection, been generally recognised that an important stage towards stepping up of the development of these areas would be the formulation of detailed plans which would be based specifically on the assessment of local potentials, problems and priorities. In pursuance of these objectives, the Planning Commission set up in 1971 a Committee of Direction consisting of senior officers of the Government of India and the Uttar Pradesh Government under the chairmanship of a Member of the Planning Commission.
Planning Commission
Planning Commission